Indonesian Passive Sentence Construction on Writing among Beginner Foreign Students - Dina Novia Rosyida; Nurchasanah Nurchasanah; Imam Agus Basuki (Jurnal Pendidikan Humaniora, 2021)
Abstract: This research aims to determine the form of Indonesian passive sentence in the essays of foreign students from America in beginner-level. The form of the passive sentence in the essay is analyzed based on the formation of the verb that fills the predicate function in the sentence. The approach used in this research is a qualitative approach with the type of text analysis research. The data in this study are in the form of passive sentences contained in the essays of foreign students from America in beginner-level. The data analysis technique in this study was carried out in 3 (three) stages, namely data reduction, data presentation, and drawing conclusions. From the results of this study, 62 data were obtained showing 4 (four) forms of passive sentences, namely (1) passive sentences predicated on verbs formed by di-, (2) passive sentences with predicated verbs formed by ter-, (3) passive sentences with predicated verbs formed by personal pronouns., and (4) passive sentences with predicated verbs formed by names.Keywords: passive sentence, passive verb form, BIPA for beginner, foreign studentsAbstrak: Penelitian ini bertujuan untuk mengetahui bentuk kalimat pasif bahasa Indonesia dalam karangan mahasiswa asing level pemula asal Amerika. Bentuk kalimat pasif dalam karangan dianalisis berdasarkan bentukan verba yang mengisi fungsi predikat dalam kalimat. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis penelitian analisis teks. Data dalam penelitian ini berupa kalimat pasif yang terdapat dalam karangan mahasiswa asing level pemula asal Amerika. Teknik analisis data pada penelitian ini dilakukan dalam 3 (tiga) tahap, yakni reduksi data, penyajian data, dan penarikan simpulan. Dari hasil penelitian ini diperoleh  62 data yang menunjukkan 4 (empat) bentuk kalimat pasif, yakni (1) kalimat pasif berpredikat verba bentukan di-, (2) kalimat pasif berpredikat verba bentukan ter-, (3) kalimat pasif berpredikat verba bentukan pronomina persona, dan (4) kalimat pasif berpredikat verba bentukan nama.Keywords: kalimat pasif, verba pasif, BIPA level pemula, mahasiswa asing